False positive results: a challenge for laboratory physicians and hematologists in treating multiple myeloma with daratumumab. Issue 1 (31st December 2022) - Liang, Shanshan; Feng, Weihua; Ma, Hongbing; Zhang, Li; Jia, Chengyao
ABSTRACT: Daratumumab injection was approved by China in 2019 for the treatment of recurrent or refractory multiple myeloma. However, the molecular weight of daratumumab, an immunoglobin G1 kappa human monoclonal antibody, was similar to that of M protein and could not be distinguished from IgG κ M protein in SPEP and SIFE. It might lead to false-positive detection resulting in misdiagnose and confusing evaluation of therapeutic response, especially for patients with IgG κ M proteins. Herein, we reported two cases encountered in our daily clinical work. These two case reports could serve as a reminder to global hematologists who have not yet started or just begun to use the drug of daratumumab.